KLASIFIKASI BANK SOAL BERDASARKAN KOMPETENSI DASAR MENGGUNAKAN ALGORITMA WINNOWING - Azis Suroni; Endang Setyati Setyati (Antivirus : Jurnal Ilmiah Teknik Informatika, 2021)
The world of education in Indonesia needs to prepare students to face the increasingly complex challenges of the 21st century. They must be able to think critically, creatively, innovatively and be able to solve problems. In this case, it is necessary to measure student learning outcomes by conducting assessments both in writing and orally. In a written assessment, an educator is expected to have many different question banks so that they can measure the maximum achievement of student competencies. The large number of question banks sometimes makes it difficult for educators / teachers to sort out questions to measure the extent to which students are successful in achieving certain competencies. With the winnowing algorithm, the questions in the question bank are compared with the existing basic competencies using the Jackard Similarity Coefficient to determine which basic competency questions belong to. With this research, it is hoped that it will make it easier for educators to sort out questions in the question bank and make it easier to find out student achievements in certain basic competencies.